CAS and PSI increase coronal alignment accuracy and reduce outliers when compared to traditional technique of medial open wedge high tibial osteotomy: a meta-analysis - Cerciello, S.; Ollivier, M.; Corona, K.; Kaocoglu, B.; Seil, R. (SPRINGER, 2022)
Purpose Medial open-wedge high tibial osteotomy (MOWHTO) is an accepted option in the treatment of medial compartment osteoarthritis of the knee in young and active patients. Functional results are closely correlated to the correction of the mechanical axis of the lower limb. Although several angular and geometrical methods and values have been proposed in the past, the ideal target is still debated. In addition, it is important to have a deep correlation between the planned correction and the achieved correction after surgery. The aim of the present systematic review was to identify the ideal coronal correction after MOWHTO and the most accurate method to achieve it. Methods A systematic review of the literature was completed on July 3rd 2020 in the Pubmed, Medline, Cochrane Reviews, and Google Scholar databases using the Medical Subject Headings (MeSH) terms: ``high tibial osteotomy{''} AND ``accuracy{''} OR ``planning{''}. Results 28 studies were included

18 were focused on computer-assisted surgery (CAS) and 10 on patient-specific instrumentation (PSI). There were 598 patients in the CAS group and 501 in the control group

the rate of outliers was 16\% and 38.2\% respectively (P = 0.04), while there was no significant difference between the two groups (SMD = - 0.10

95\% CI 1.31 to 1.12

P = n.s.) in terms of coronal accuracy. Likewise, there were 318 patients in the PSI group and 40 in the control group

the rate of outliers was 15\% and 40\% respectively (P = 0.98), while there was no significant difference between the two groups (SMD = 0.01

95\% CI 0.58 to 0.59

P = 0.98). Conclusions A statistically significant reduced outlier rate and a non-significant increased accuracy emerged with the use of CAS when compared to the traditional surgical technique, whereas the results of PSI were still inconclusive. In addition, it emerged clearly that no consensus still exists on the ideal correction target to be achieved after surgery.
Keywords: High tibial osteotomy; Medial open wedge; Accuracy; Coronal alignment; Computer assisted surgery; Patient specific instrumentation